Proposed Innovation Leadership Framework for Risk Based Strategic Decision?Making and Value Creation: A Case Study from the Indonesian Plastic Manufacturing Company - Fahmmy Herdiansyah Heryadi; Sylviana Maya Damayanti (Journal Research of Social Science, Economics, and Management, 2026)
Innovation has become an important requirement for organizations seeking to maintain competitiveness and achieve sustainable growth. However, many organizations still face challenges in transforming innovation initiatives into sustainable organizational capabilities. This study aims to assess the organization’s innovation readiness, identify capability gaps, analyze their root causes, and develop a Proposed Innovation Leadership Framework. A qualitative case study was conducted in an Indonesian plastic manufacturing company through interviews with key leaders and analysis of organizational documents. The findings indicate that the organization has demonstrated a strong commitment to innovation and implemented various innovation initiatives. However, challenges remain in governance, organizational learning, strategic alignment, and capability development, limiting the organization’s ability to build sustainable innovation capability. Based on these findings, this study proposes an Innovation Leadership Framework to strengthen innovation capability, support risk-based strategic decision making, and enhance value creation. The framework emphasizes leadership involvement, effective governance, organizational learning, and long-term capability development to enable innovation as a sustainable source of competitive advantage.